Polynomial Solutions Modulo ˢ of Differential KZ and Dynamical Equations - Etingof, Pavel; Varchenko, Alexander (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
We construct polynomial solutions modulo ˢ of the differential KZ and dynamical equations, where is an odd prime number.